2006
DOI: 10.1063/1.2203631
|View full text |Cite
|
Sign up to set email alerts
|

Test of classical nucleation theory on deeply supercooled high-pressure simulated silica

Abstract: We test classical nucleation theory (CNT) in the case of simulations of deeply supercooled, high density liquid silica, as modelled by the BKS potential. We find that at density ρ = 4.38 g/cm 3 , spontaneous nucleation of crystalline stishovite occurs in conventional molecular dynamics simulations at temperature T = 3000 K, and we evaluate the nucleation rate J directly at this T via "brute force" sampling of nucleation events in numerous independent runs. We then use parallel, constrained Monte Carlo simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Below, we compare our results for a against β| μ|, as some studies suggest a very good correspondence, 8,9,41 and justify our assumption that b is equal to βγ up to a constant factor which depends on the shape and density of the crystallites. Recently, it has been shown for a soft-core colloidal model that the procedure we follow here for determining n may not be sufficient for describing crystal-like structures, but that the scaling represented by Eq.…”
Section: B Fitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Below, we compare our results for a against β| μ|, as some studies suggest a very good correspondence, 8,9,41 and justify our assumption that b is equal to βγ up to a constant factor which depends on the shape and density of the crystallites. Recently, it has been shown for a soft-core colloidal model that the procedure we follow here for determining n may not be sufficient for describing crystal-like structures, but that the scaling represented by Eq.…”
Section: B Fitsmentioning
confidence: 99%
“…On the other hand, it is somewhat perplexing that such a large rescaling is required at all. In a few previous studies, comparison between a and β μ has shown that in some cases a close correspondence is observed, 8,9,41 while, in principle, the value of a should vary with the definition crystallike particles. There are several potential reasons why such a disagreement can be found.…”
Section: E a Vs β μmentioning
confidence: 99%
“…After a very short time, ∆n 2 (t) enters a diffusive regime [52], i.e., it becomes linear in time, and one obtains in this regime,…”
Section: Attachment Ratementioning
confidence: 99%
“…The presented equilibrium phase diagram will serve as a starting point for studies of crystal nucleation in tetrahedral liquids. [16][17][18][19] …”
Section: Introductionmentioning
confidence: 99%